PENGARUH VARIASI LATIHAN TERHADAP PENINGKATAN KETERAMPILAN BERMAIN SEPAK BOLA PADA CLUB PUTRA BAJA FC TAHUN 2017 - Quddus, Abbdul; dinata, karno; Daniyantara, Didik (Universitas Hamzanwadi, 2018)
In this study aims to determine whether or not the influence of exercise variation on the Improvement of Football Playing Skills at Club Puta Baya FC 2017?